Compliance with the anti-trafficking protocol - Cho, Seo-Young; Vadlamannati, Krishna Chaitanya (European journal of political economy, 2012)
The Anti-trafficking Protocol reflects the interests of the major countries. Due to the high costs of compliance, countries will strategically select those obligations that will satisfy the major countries most efficiently with lower costs of compliance. Among the three main obligations of the Protocol - prevention, protection and prosecution - we predict that ratification leads to the strongest effect on compliance with the prevention policy because prevention reflects the key interests of the major countries, while triggering less domestic resistance and political costs to implement. Therefore, it is the most ‘efficient’ form of compliance. We empirically test this hypothesis by employing panel data from 147 countries during the period of 2001-2009. As the theory predicts, the ratification of the Protocol has the strongest effect on the prevention policy of a member state compared to protection and prosecution.